Enhanced Hard-magnetic Properties of Rare Earth-free L10-FeNi Phase in FeNiPC Alloys - Han, Jonghee; Suh, Jin-Yoo; Son, Hyunsol; Choi-Yim, Haein (한국자기학회, 2021)
In this study, FeNi-based amorphous alloys having crystallization temperature (Tx) close to FeNi order-disorder transition temperature were developed. Through an extended annealing process at around the crystallization temperature, an ordered phase, L10-FeNi, was formed. Structural characterizations of annealed ribbons confirmed the formation of L10-FeNi phase through observation of a weak superlattice peak. Measured coercivity (Hc) also indicated formation of the ordered L10-FeNi phase, which increased up to 744 Oe after the annealing process. ？ The Korean Magnetics Society. All rights reserved.